Green Synthesis of Carbon Quantum Dots from Coffea Arabica Residue: Comparison Between Pyrolysis and Microwaves (Journal SCIENCEVOLUTION, 2026)
Carbon quantum dots (CQDs) are fluorescent nanomaterials widely studied due to their low toxicity and remarkable optical properties, which enable their use in various applications. Agro-industrial residues, such as Coffea arabica waste, represent a sustainable carbon source for nanomaterial synthesis within circular economy strategies. The objective of this study was to evaluate the effect of two green synthesis routes, pyrolysis and microwave-assisted synthesis, on the structural and optical properties of CQDs obtained from spent coffee grounds. The precursor was pretreated for 24 hours and subsequently subjected to thermal pyrolysis at 400°C under controlled conditions, whereas the microwave-assisted method employed irradiation at 750 W and 200°C. The obtained samples were purified and characterized using photoluminescence spectroscopy and X-ray diffraction. CQDs synthesized via pyrolysis exhibited a blue emissions (440–460 nm) with particle diameters between 10 and 12 nm, whereas the microwave method produced emissions around 345 nm with particle diameters ~8 nm. The results indicated that pyrolysis produces higher fluorescence intensity, highlighting its potential for optoelectronic applications.
Keywords: Carbon Quantum Dots; Nanomaterial; Green Synthesis; Coffee Waste Valorization; Pyrolysis; Microwave-Assisted; Fluorescence